Penerapan Metode Rapid Application Development dalam Pengembangan Sistem Informasi Perpustakaan pada SMA Negeri 2 Kota Lubuklinggau - Shinta Aprilisa; Putri Yuma Maharani; Septa Arwansa; Rangga Borneo Pratama (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This study aims to develop a web-based library information system at SMA Negeri 2 Lubuklinggau using the Rapid Application Development (RAD) method. The research was motivated by library management activities that were still dominated by manual recording, which caused data redundancy, delays in searching book collections, difficulty tracking borrowing and returning transactions, and inefficient report preparation. This study used an applied system development approach with data collected through observation, interviews, and literature study. The RAD stages consisted of requirements planning, design workshop, and implementation. The system design included a logical record structure, sequence diagram, and interface prototype, while functional validation was conducted using black-box testing. The results show that the system can manage book data, member data, borrowing transactions, return transactions, and library reports. Black-box testing indicates that the main functional features run according to the expected scenarios. Therefore, the RAD method is suitable for developing a school library information system because it supports rapid prototyping, active user involvement, and iterative improvement based on operational needs.